Design Thinking as a Strategic Approach to E-Participation: From Current Barriers to Opportunities - Mariani, Ilaria; Mortati, Marzia; Rizzo, Francesca; Deserti, Alessandro (SpringerBriefs in Applied Sciences and Technology; PoliMI SpringerBriefs, 2025)
This open access book examines how the adoption of Design Thinking (DT) can support public organisations in overcoming some of the current barriers in e-participation. Scholars have discussed the adoption of technology to strengthen public engagement through e-participation, streamline and enhance the relationship between government and society, and improve accessibility and effectiveness. However, barriers persist, necessitating further research in this area. By analysing e-participation barriers emerging from the literature and aligning them with notions in the DT literature, this book identifies five core DT practices to enhance e-participation: (i) Meaning creation and sense-making, (ii) Publics formation, (iii) Co-production, (iv) Experimentation and prototyping, and (v) Changing organisational culture. As a result, this book provides insights into enhancing tech-aided public engagement and promoting inclusivity for translating citizen input into tangible service implementations. The book triangulates qualitative analysis of relevant literature in the fields of e-participation and DT with knowledge from European projects experimenting with public participation activities implying experimentation with digital tools. This research aims to bridge the gap between theoretical frameworks and practical application, ultimately contributing to more effective e-participation and digital public services.